MODEL OF TRANSPORT AND LOGISTICS SYSTEM ORGANIZATION IN THE CONCEPT OF SUSTAINABLE DEVELOPMENT - STEHNEI, Marianna; NOD, Orshoia; MEISAR, Bohdan; HRYNCHAK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article addresses the problems of forming and implementing a model of sustainable development for transport and logistics systems in Ukraine. The purpose of this article is to investigate the current state of the transport and logistics system and to justify a model for the sustainable development of Ukraine's transport and logistics system.An assessment of the current state of the transport and logistics system and its position in Ukraine's global competitiveness was conducted. The rise in the global competitiveness ranking prior to the military invasion was associated with increased capital investments in transport infrastructure development. However, it has been proven that the level of infrastructure provision and the organization of transport and logistics services are not sufficient for integration into the unified transport system of the EU. The transport and logistics system also does not meet the social and environmental standards adopted in European Union countries, which necessitates a review of the existing model based on sustainable development principles.The state and main priorities of investment support for transport systems were analyzed. It has been proven that the development of transport and logistics infrastructure in Ukraine, both during and after the post-war recovery period, despite significant damages and losses, presents new challenges and opportunities for the economy to create an innovation-oriented transport and logistics model for sustainable development. A model for the sustainable development of transport and logistics systems in Ukraine was proposed, which balances and integrates the main vectors (economic, social, environmental), tasks within the defined vectors, and tools for their implementation.To implement the sustainable development model of transport and logistics systems, a comprehensive mechanism and tools need to be developed, including: territory planning, standardization, development of international projects, public-private partnerships, economic incentives, and the introduction of innovations. This will ensure the integration of Ukrainian transport and logistics infrastructure into global economic networks, enhancing its competitiveness and environmental sustainability.
Keywords: transport and logistics system; sustainable development model; quality of transport infrastructure; investments; implementation tools